Somatics and Physical Fitness of Selected Military Classes - Marian Rzepko; Adam Kozubal; Paweł Ostrowski; Zbigniew Trębacz; Waldemar Tłuczek; Łukasz Chlastawa; Sławomir Drozd (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2024)
The idea of opening military classes refers to the tradition of national defense education, training the young generation to defend the homeland and strengthening the country's ties with the army. The creation of military classes became a precedent for the Ministry of National Defense and the Ministry of National Education to build a common defense education system for high school students. The task of military classes in Polish high schools is to prepare young people for future service in various services, such as police, fire brigades and other special services. The aim of this work is to capture the relationship between body composition components and physical fitness of selected uniformed groups. The body composition components were analyzed with the help of the Tanita Body Composition Analyzer DC-240MA. The study used tests from the Polish Army physical fitness test, the Beep test and barbell bench press while lying on a straight bench. One of the conclusions obtained was that the correlation between body composition and fitness tests showed that higher levels of body fat, lean body mass, BMI and body weight negatively affect the results obtained in pull-ups, trunk bends, shuttle runs and Beep tests.